2016
DOI: 10.1519/jsc.0000000000001177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypohydration on Repeated 40-yd Sprint Performance

Abstract: This study examined the effects of hypohydration on repeated 40-yd sprint performance. Anaerobically fit current and former Division II male athletes (n = 12) completed 2 bouts of 10 × 40-yd sprints followed by an agility test, dehydrated (∼3% body weight [DT]), or hydrated trial (HT). Statistical analysis of group means indicated that hypohydration had little effect on sprint times for either the first (DT= 5.38 ± 0.37; HT = 5.35 ± 0.34) or second (DT = 5.47 ± 0.39; HT = 5.42 ± 0.39) bout of 10 sprints with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Davis et al (Davis et al, 2015) included RPE measures when examining intermittent sprinting and hydration state and found that when subject were hypohydrated, they expressed greater RPE values over euhydration after each bout of sprints. Additionally, Gann et al (Gann et al, 2016) showed that across multiple bouts of repeated sprints the dehydrated condition showed higher RPE measures than hydrated conditions. This trend was seen across multiple trials within the same bout.…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al (Davis et al, 2015) included RPE measures when examining intermittent sprinting and hydration state and found that when subject were hypohydrated, they expressed greater RPE values over euhydration after each bout of sprints. Additionally, Gann et al (Gann et al, 2016) showed that across multiple bouts of repeated sprints the dehydrated condition showed higher RPE measures than hydrated conditions. This trend was seen across multiple trials within the same bout.…”
Section: Discussionmentioning
confidence: 99%